Elaboración de un plan de comunicación digital para las redes sociales de la gobernación de la provincia de El Oro. - Bermeo Neira, Alfonso Enrique (Machala, 2020)
The following research paper compiles information from several Social Networks that were selected according to their popularity among Ecuadorians, each Social Network was characterized according to its functions, and finally the specific audience that predominates in each of these was identified. The objective of the research was to analyze the use of Social Networks in the Government of the Province of El Oro to communicate to citizens, and thus be able to propose a Digital Communication Plan proposal, for that it was necessary to know all the digital part, its channels, the appropriate type of message and the public that predominates in each of these channels. Interviews were conducted with specialists in the area of Digital Communication on the objective and benefits of developing a Digital Communication Plan, their responses served to design a proposal focused on highlighting the image of the institution, generating traffic and better interaction with the user in Networks Social. A closed interview was also conducted with the Communication Analyst of the Government of the Province of El Oro, which helped to contrast the investigation and obtain a diagnosis of the use that is given to the Social Networks. The investigation concludes that the Government of the Province of El Oro loses visibility in the middle, since it focuses on making publications constantly on its main Social Networks (Facebook and Twitter), leaving aside its other Social Networks (YouTube and Instagram).
El siguiente trabajo de investigación compila información de varias Redes Sociales que fueron seleccionadas según su popularidad entre los ecuatorianos, cada Red Social fue caracterizada según sus funciones, y finalmente se identificó el público específico que predomina en cada una de estas. El objetivo de la investigación fue analizar el uso que se le dan a las Redes Sociales en la Gobernación de la Provincia de El Oro para comunicar a los ciudadanos, y así poder plantear una propuesta de Plan de Comunicación Digital, para eso fué necesario conocer toda la parte digital, sus canales, el tipo de mensaje adecuado y el público que predomina en cada uno de estos canales. Se realizaron entrevistas a especialistas en el área de Comunicación Digital sobre el objetivo y beneficios de elaborar un Plan de Comunicación Digital, sus respuestas sirvieron para diseñar una propuesta enfocada en resaltar la imagen de la institución, generar tráfico y mejor interacción con el usuario en Redes Sociales. También se realizó una entrevista cerrada a la Analista de Comunicación de la Gobernación de la Provincia de El Oro, que ayudó a contrastar la investigación y obtener un diagnóstico del uso que se le dan a las Redes Sociales. La investigación concluye que la Gobernación de la Provincia de El Oro pierde visibilidad en el medio, ya que se enfoca en realizar publicaciones constantemente en sus Redes Sociales principales (Facebook y Twitter), dejando de lado a sus otras Redes Sociales (YouTube e Instagram).
Keywords: RED SOCIAL; COMUNICACION DIGITAL; FACEBOOK; YOUTUBE